Los jesuitas y su labor evangelizadora en la doctrina de Santiago del Cercado - Rodríguez Q., David (2005)
The arrival of Jesuits to Peru in 1568 coincided with the beginning of the breakdown of the indigenous order as a result of different modalities of intervention designed by the Spanish crown regime in order to rule its American possessions, according to the organization of the new administration directed by the viceroy Francisco de Toledo (1569-1581). Is in this context the successful evangelization work developed by the Jesuits must be understood, as seen in the model reproduced by the doctrine of Santiago del Cercado. This effectiveness has to be understood not only by considering the particularity of the methods that were innovated or refined by the members of this religious order, but also taking into account the support that they received from the colonial administration. These intentions were part of the Spanish crown regime’s attempt to gain political and ideological control over the population.